2002
DOI: 10.1038/sj.ejhg.5200881
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene, FAM11A, associated with the FRAXF CpG island is transcriptionally silent in FRAXF full mutation

Abstract: The cytogenetic expression of the FRAXF fragile site is due to an expanded, hypermethylated and unstable CGG repeat in Xq28. Normal individuals have 6 -38 triplet repeats while individuals expressing the fragile site have expansions of greater than 300 triplets. Through analysis of the region adjacent to the fragile site, we have identified a *2.6 kb cDNA originating from the FRAXF fragile site associated CpG island, and containing the unstable FRAXF CGG repeat in its 5' UTR region. This gene, FAM11A, comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…We have shown that in vitro treatment with 5-azadC of fragile X cells leads to reactivation of FMR1 transcription (Chiurazzi et al, 1998), after causing passive DNA demethylation (Pietrobono et al, 2002). Furthermore, we recently proved that treating cell lines of FRAXF individuals with 5-azadC also causes transcriptional reactivation of the FAM11A gene (Shaw et al, 2002).…”
Section: Reactivation Of Genes With a Methylated Cpg Islandmentioning
confidence: 95%
“…We have shown that in vitro treatment with 5-azadC of fragile X cells leads to reactivation of FMR1 transcription (Chiurazzi et al, 1998), after causing passive DNA demethylation (Pietrobono et al, 2002). Furthermore, we recently proved that treating cell lines of FRAXF individuals with 5-azadC also causes transcriptional reactivation of the FAM11A gene (Shaw et al, 2002).…”
Section: Reactivation Of Genes With a Methylated Cpg Islandmentioning
confidence: 95%
“…MAGEA11 encodes a highly conserved protein that modulates the androgen receptor and may have an important role in phenotypic sex determination and prostate cancer [Jurk et al, 1998;Chomez et al, 2001;Bai et al, 2005]. The TMEM185A promoter contains the FRAXF fragile site and its transcription is completely eliminated by full expansion of FRAXF [Shaw et al, 2002]. However, no physiological defect was observed in a male with this gene silencing, so it appears that neither an increase (as seen here) nor decrease (as reported by Shaw et al [2002]) of one copy of TMEM185A causes an obvious phenotype.…”
Section: Pathological E¡ect Of the Double Complex Mutationsmentioning
confidence: 99%
“…Other genes that, like the fully mutated FMR1, have a methylated CpG island, require also DNA demethylation in order to resume transcription. We have actually shown that 5-azadC treatment is also effective in turning on the FAM11A gene associated with the Xq28 folate-sensitive fragile site, that is transcriptionally silent in FRAXF full mutations [Shaw et al, 2002]. The same effect might be expected for the other fragile sites due to a CGG repeat expansion followed by DNA methylation (e.g., FRAXE, FRA16A, etc.)…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 73%